DETEKSI DINI PENYAKIT IUGR (INTRA UTERINE GROWTH RETRICTION) DENGAN METODE SVM (SUPPORT VECTOR MACHINE) - irhama karin karinasari (Lambung Mangkurat University, 2020)
IUGR (INTRA UTERINE GROWTH RETRICTION) is a condition when the baby's growth stops before birth so the baby looks small and does not have normal growth like normal fetal growth patterns. The purpose of this study was to detect the fetus in the womb so as to know the condition of the baby is normal or IUGR by knowing the gestational age, bi-parietal diameter, abdominal circumference, head circumference, fetal length.The purpose of this study was to obtain an accurate prediction of IUGR with